Analysis of Perceptions and Interests of Accounting Students in Choosing A Professionin the Field of Taxation (Case Study of Tax Concentration at University West Sulawesi) - Muhammad Mukhram; Nurjannah; Wulan Ayuandiani (ASIAN PUBLISHER, 2023)
Profession in the field of taxation is one of the professions that are sought after and rarely in demand and is taken as a concentration by accounting students. Profession in the field of taxation is currently urgently needed because the number of employees in the field of taxation is still small and taxes are a source of state revenue in financing state expenditures. This study aims to find out how the perceptions and interests of accounting students in choosing a profession in the field of taxation at the University of West Sulawesi. Through a frame of mind that begins with accounting students then looks for their perceptions and interests using each indicator and then measures them with a Likert scale and Guttman scale and then describes them in a narrative manner so as to produce different perceptions and interests. The informants in this study were 15 tax concentration students from the 2018-2020 class at the economics faculty. The method used is descriptive qualitative. The results in this study are that the perceptions of students in choosing a profession in the field of taxation are different and positive. Students' interest in choosing a profession in the field of taxation varies, but the difference is positive.